2005
DOI: 10.4161/cc.4.9.1985
|View full text |Cite
|
Sign up to set email alerts
|

New and Old Functions of STAT3: A Pivitol Target for Individualized Treatment of Cancer

Abstract: Signal transducers and activators of transcription (STAT) regulate a plethora of cytokine responses. Recently, aberrant signaling by STAT proteins has been demonstrated to play important roles in the pathogenesis of many neoplasms, by promoting cell cycle progression and survival, stimulating angiogenesis, and impairing immunological responses and tumor surveillance. We have developed genetic tools to evaluate STAT-dependent malignancy and showed that survival and growth of lymphoid malignancies requires expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 15 publications
0
95
0
2
Order By: Relevance
“…4 In the present study, we investigated the activity of the novel multitargeted TKI EXEL-0862 against the human FIP1L1-PDGFR-a-expressing cells to determine whether this compound might be a potential candidate for clinical development in patients with HES. We documented that 24,27 and Erk1/2 enhances the activity of anti-apoptotic Bcl-2 family members, such as Bcl-2 and Mcl-1. 28,29 Collectively, our data suggested that EXEL-0862 decreased proliferation and induced apoptosis through ablation of STAT3 and Erk1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…4 In the present study, we investigated the activity of the novel multitargeted TKI EXEL-0862 against the human FIP1L1-PDGFR-a-expressing cells to determine whether this compound might be a potential candidate for clinical development in patients with HES. We documented that 24,27 and Erk1/2 enhances the activity of anti-apoptotic Bcl-2 family members, such as Bcl-2 and Mcl-1. 28,29 Collectively, our data suggested that EXEL-0862 decreased proliferation and induced apoptosis through ablation of STAT3 and Erk1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Given this strict dependence on STAT3 for survival, it is puzzling to find that a few tumors can still develop in the complete absence of STAT3 in both the DEN-induced HCC model and in NPM-ALK transgenic mice [65,79]. It is plausible that an alternative pathway can be activated in STAT3-null tumors but this pathway is hardly active in the presence of STAT3 [78].…”
Section: Stat3 Promotes Hcc Development In Mouse Modelsmentioning
confidence: 99%
“…Using such conditional STAT3 knockout mice, it has been shown that STAT3 is required for tumorigenesis in mouse skin [75], intestine [76,77] and liver [65]. Such results left little doubt that STAT3 is a critical oncogenic transcription factor and an attractive target for cancer therapy [78].…”
Section: Stat3 Promotes Hcc Development In Mouse Modelsmentioning
confidence: 99%
“…Considerable effort is currently being focused on finding compounds capable of inhibiting various aspects of STAT3 function, through the inhibition of phosphorylation, dimerization, and DNA binding of STAT3 (Inghirami et al, 2005). SOCS1 reportedly suppressed STAT3 activation in a subset of hepatocellular carcinoma cells with STAT3 phosphorylated by JAKs (Yoshikawa et al, 2001).…”
Section: Crif1-and Stat3-mediated Transformationmentioning
confidence: 99%